Exploring (bio)catalytic activities of structurally characterised Cu(ii) and Mn(iii) complexes: histidine recognition and photocatalytic application of Cu(ii) complex and derived CuO nano-cubes. Issue 39 (19th September 2018) - Kumari, Babli; Kundu, Samapti; Ghosh, Kajari; Banerjee, Mahuya; Pradhan, Swapan Kumar; Islam, Sk. Manirul; Brandão, Paula; Félix, Vítor; Das, Debasis
Abstract : The multifunctional properties of two polymeric complexes of Cu(ii ) and Mn(iii ) have been evaluated. Abstract : Structurally characterised two polymeric complexes of Cu(ii ) (3 ) and Mn(iii ) (4 ) of the ligand L (2-(((2-(phenylamino)ethyl)imino)methyl)phenol) have been explored for catecholase-like activity, fluorescence recognition of histidine and catalytic activity towards coupling of aryl iodides with benzamide, leading to N -arylbenzamides. CuO nano-cubes (NCs) prepared by thermal decomposition of the Cu(ii ) complex function as photocatalysts for the degradation of methylene blue. Cube-like morphology of CuO nanocrystal and flake-shaped micrometer order Cu(ii ) complex have been established from the field emissive scanning electron microscopy (FESEM) images.